Left Ventricular Hypertrophy and Clinical Outcomes in Heart Failure Patients Based on Hypertension Subtypes: Insights from a Tertiary Hospital Heart Failure Registry in Malang, Indonesia - Budi Satrijo; Andona Murni Maharani; Muhammad Rizki Fadlan; Shalahuddin Suryo Baskoro (Heart Science Journal, 2023)
BackgroundLeft ventricular hypertrophy (LVH) is a maladaptive response to chronic pressure overload and an important risk factor sudden death in patients with heart failure. Previous studies show that LVH is a risk factor for systolic heart failure. It’s interesting to examine whether Isolated Systolic Hypertension (ISH) in the presence of LVH contribute to clinical outcome.Objective: The aims of this study to examined association of  ISH with cardiovascular outcomes and to examined associations of ISH and LVH  in Heart failure registry patientMethods: A total of 120 subject’s were collected from Saiful Anwar Heart Failure Registry from January 2019 to December 2019. All participants were individually interviewed with a structured questionnaire  for collecting baseline characteristic. Subject were classified into 2 group of hypertension (ISH and Systolic Diastolic Hypertension (SDH)). ISH based on the criteria of SBP ≥ 140 and DBP < 90 mmHg and SDH based on SBP ≥ 140 and DBP ≥ 90 mmHg. The EF and volumes were measured with 2D-biplane Simpson's method by measured as a standart mannerResult’s: ISH commonly found among older hypertensive patients than SDH (Mean age 61,23±11,2 yo  vs  53,52±11,1 yo, respectively, p<0,04)). LVH was more prevalence among ISH  than SDH. No difference in clinical outcome such as in hospital mortality, Rehospitalization, and Lengt of stay were observed in both groups. Complication of hypertension was similar in both groups such as stroke, Myocardial Infarct, and Chronic Kidney Disease. Intrestingly, no difference also observe in compliance to the drug between ISH and SDH. We also examined subgroup analysis of subject’s with ISH. There was no statistically significant difference in clinical outcome between ISH with LVH and ISH without LVH.Conclusion: In this study, we suggest that ISH more common in older patient with HF than SDH  but had similar associations with cardiovascular mortality and rehospitalization. ISH was associated with a higher prevalence of left ventricular hypertrophy than SDH.